Stability and Control Assessment of an Aerial Target Drone Based on a Scale Model of A-4 Skyhawk Jet Fighter - Bakar, Abu Zaid (2009)
A-4 Skyhawk is a jetfighter aircraft which was bought by our Royal Malaysia Air Force (RMAF) back in the year 1980s. The study is to evaluate the stability and control aspects of the design of A-4 Skyhawk as a target drone with a scale of one third. The condition of the studies involve the longitudinal and lateral controls of the open loop derivatives at the sea level and 10,000 feet altitude, for ranges of Mach number of 0.2, 0.3, 0.4, 0.5 and 0.6. Hence, the closed loop derivatives shall be designed to cater for the unsatisfactory parameters. With the usage of stability software such as the United State Air Force Stability and Control DATCOM (USAF DATCOM), analysis softwares such as MATLAB and CATIA, the method of design concept shall be more viable in order to produce a stable design. The USAF DATCOM software is used to generate the static and dynamic aerodynamic derivatives of the given aircraft. MATLAB is mathematical software used to perform high speed and massive calculations. MATLAB is used to obtain the transfer function of the aircraft equation of motion, to perform stability analysis and to plot the stability related graphs. The CATIA software is used to develop the full scale and scale size model of the A-4 Skyhawk jetfighter. From this software the scale model dimension, estimated weight and second moment of inertia is obtained. Thus, combination of all the software and calculation, the output of the study shall be able to meet the objectives of the study. It was found that, for the open loop derivatives of the longitudinal motion, the flying qualities for both short period and phugoid modes felt in the Level 2 category. As for the lateral motion, the flying qualities of the Dutch roll, spiral and roll modes felt in the Level 1 category as described by the Cooper-Harper scale. However, the critical scenario for the longitudinal and lateral for both the sea level and 10,000 feet altitude occurred at the speed of Mach number 0.2, where it had the most oscillatory conditions and the least settle for steady state condition. This may due to the less effectiveness of the delta wing at low speed flying condition.